Hepatic endoplasmic reticulum calcium fluxes: effect of free fatty acids and KATP channel involvement. Issue 2 (26th February 2021) - Al-Rawi, Rawan; Wang, Xudong; McCormick, Kenneth
Abstract: As a common sequel to obesity, plasma and intracellular free fatty acid (FFA) concentrations are elevated and, as a consequence, manifold disturbances in metabolism may ensue. Biochemical processes in the cytosol and organelles, such as mitochondria and endoplasmic reticulum (ER), can be disturbed. In the ER, the maintenance of a high calcium gradient is indispensable for viability. In sarcoplasmic reticulum, selective FFA can induce ER stress by disrupting luminal calcium homeostasis; however, there are limited studies in hepatic microsomes. Our studies found that FFA has a noxious effect on rat hepatic microsomal calcium flux, and the extent of which depended on the number of double bonds and charge. Furthermore, insofar as the FFA had no effect on microsomal calcium efflux, their inhibitory action primarily involves calcium influx. Finally, other cationic channels have been found in hepatic ER, and evidence is presented of their interaction with the Ca 2+ ATPase pump.